2018
DOI: 10.1002/chem.201804195
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (±)‐Merrilactone A by a Desymmetrization Strategy

Abstract: A concise synthesis of (±)-merrilactone A has been accomplished featuring desymmetrization of a C -symmetric dilactone, Rh -catalyzed intramolecular hydroacylation of a 4-alkynal, and Ti -mediated reductive radical cyclization of epoxy-allene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…At this stage, we achieved the most challenging transformation in the synthesis: a mild photoinduced desaturation in a complex hydrocarbon system. This success eliminated the protection manipulation of the labile C7 alcohol, which usually occurred in the previous synthetic efforts. The spectroscopic data of 6 are consistent with those reported . Interestingly, masking the C-7 alcohol as an acetate only led to the corresponding olefin product with a moderate yield (see the Supporting Information for more details).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…At this stage, we achieved the most challenging transformation in the synthesis: a mild photoinduced desaturation in a complex hydrocarbon system. This success eliminated the protection manipulation of the labile C7 alcohol, which usually occurred in the previous synthetic efforts. The spectroscopic data of 6 are consistent with those reported . Interestingly, masking the C-7 alcohol as an acetate only led to the corresponding olefin product with a moderate yield (see the Supporting Information for more details).…”
Section: Resultssupporting
confidence: 75%
“…To date, over 100 sesquiterpenes with diverse oxygenation patterns have been discovered from this genus of plants and display notable biological activities, including antiviral, neurotoxic, and neurotrophic effects. Among them, (−)-merrilactone A ( 7 , Figure C) (anislactone type), which exhibited prominent neurotrophic activities at remarkably low concentrations (100 nM), has received the most attention from the synthetic community with several creative syntheses reported. Although these sesquiterpenes hold the promise for the treatment of neurodegenerative disorders associated with Alzheimer’s and Parkinson’s diseases, most biological studies are restricted to cell-culture-based assays due to low natural product abundance and limited choices of synthetic derivatives. Moreover, the molecular mechanism underlying the neurotrophic effect of Illicium sesquiterpenes remains unclear. Here, we disclose a unique site-selective desaturation strategy to access five anislatone-type Illicium sesquiterpenes ( 7 – 11 , Figure C) from inexpensive ( R )-pulegone, including a 13-step synthesis of (−)-merrilactone A ( 7 ) on a gram scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several different routes towards the total synthesis of merrilactone A have been reported [77,78,79,80,81]. Most recently, Liu and Wang [82] designed and achieved a concise synthesis of merrilactone A in a racemic form (Scheme 6). In their synthesis work, exploiting dimethyldioxirane (DMDO) on 27 allowed the epoxide intermediate that was subjected to acidic conditions to afford synthetic merrilactone A through the epoxide-opening oxetane formation.…”
Section: Oxetanesmentioning
confidence: 99%
“…Due to their biological activity and complex molecular structure, these compounds have attracted the interest of synthetic chemists. Numerous total syntheses and synthetic studies of these compounds have been reported, especially in the last decade [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Illisimonin A (5), isolated from Illicium simonsii in 2017, is a new sesquiterpene that has a neuroprotective effect on oxygen-glucose deprivation-induced cell injury [24].…”
Section: Introductionmentioning
confidence: 99%